Pembentukan Dasar Akhlaq Islami dan Etika Dalam Ilmu Tauhid Agama Islam - Andriani, Yayan (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2019)
The formation of the basic principles of Islam is a study or virtue of morals, the attitude that behaves towards one's character. On the other hand, Islamic morality is also an open act so that it can be an indicator of a person. Ethics in the economy of capitalism take the shelter of modernization which is a direct result of the era of globalization in the economic field. Modern capitalism, although finally able to prove its superiority over socialism, is in fact on various issues. Basically, ethics (basic values) in business functions to help business people to solve moral problems in business practice. Therefore, in order to develop an economic system, there must be an effort to revitalize trade as an economic system, both capitalism and socialism, by exploring Islamic basic values ​​regarding trade (business) rules from the Qur'an and as-sunnah which is something that is undoubtedly to be done with a frame of mind in terms of material orientation but also immaterial.